Adaptation in Pongah Si Pemungut Hutang - Mas Rynna Wati Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Adaptation is defined, as an altered or amended version of a text, one adapted for filming, broadcasting, or production on the stage from a novel or similar literary source. This form of technique is common in theatre productions these days and adaptation had successfully transformed many texts into plays. Also, adaptation in theatre can offer new perspectives on some of the issues that never grow old across time. Pongah si Pemungut Hutang was first staged during the Terengganu Theatre Festival 2019 was an adapted version taken from the popular one act love/romantic comedy, The Boor written by Anton Chekov in 1888. Even though, it was more than 200 years old, Chekov’s work has never been exhausted as perceived by many. The issue raised is still relevant in current situation, that is a husband passed away leaving a widow who had to bear the dead husband’s debts. The plot twist was when the debt collector, had fallen in love with the widow. It is found that this new version of The Boor, had transformed the scene from the original texts as a means to suit the socio- cultural background of the audience. This paper traces the elements of adaptations in this modified version of romantic comedy. It is also intended to focus on the ways in which how adaptation is still relevant in highlighting the issues that are prevalent in current days.